Is there a 'wicked problem' of small-scale coastal fisheries in Sierra Leone?. (August 2020) - Okeke-Ogbuafor, Nwamaka; Gray, Tim; Stead, Selina Marguerite
Abstract: The situation of small-scale coastal fisheries in Sierra Leone is dire, with diminishing fish stocks and fish sizes due to massive industrial fishing and widespread use of banned nets by artisanal fishers. Repeated attempts have been made by fisheries management to improve the situation, but with little or no success. Superficially, it might seem that the two main causes of the problem - foreign industrial fishing and damaging artisanal nets – could be readily dealt with, but closer analysis reveals that tackling these causes is immensely complicated. This is because their roots lie deep in Sierra Leone's history, culture and politics, and any attempt to deal with them could lead to unintended consequences which might make the situation worse not better. Does this mean there is a 'wicked problem' here – i.e. a problem so intractable that it has no practicable solution? This is the issue which the present study addresses. The research is based on extensive fieldwork carried out in two large fishing coastal fishing communities in Sierra Leone (Tombo and Goderich) during April and May 2017 when 200 open-ended questionnaires (SQs) were administered and 51 key informant interviews (KIs) were conducted. The study concludes that the situation faced by small-scale fisheries in these communities meets several, but by no means all, of the criteria of a wicked problem, and that while a definitive solution to the problem is unfeasible, stakeholders could adopt strategies to alleviate its more harmful consequences.